Laser Attack Benchmark Suite - Amornpaisannon, Burin; Diavastos, Andreas; Peh, Li Shiuan; Carlson, Trevor E. (My University, 2020)
Laser fault injection in integrated circuits is a powerful information leakage technique due to its high precision, timing accuracy and repeatability. Countermeasures to these attacks have been studied extensively. However, with most current design flows, security tests against these attacks can only be realized after chip fabrication. Restarting the complete silicon design cycle in order to address these vulnerabilities is thus both time-consuming and costly. To overcome these limitations, this paper proposes an open-source benchmark suite that allows chip designers to simulate laser attacks, and evaluate the security of their designs, both hardware-based and software-based, against laser fault injection early on during design time. The proposed benchmark suite consists of a tool that automatically integrates hardware-based spatial, temporal and hybrid redundancy techniques into a target design. With the tools used in this work, we demonstrate how the attacks can be simulated on a Verilog simulator, and run on an FPGA with a design equipped with hardware-based redundancy techniques without manual modifications. This work consists of four attacks, and four hardware-based redundancy techniques. The attacks and defenses together that the benchmark suite provides will automate the entire early design evaluation flow against laser fault injection attacks.
Keywords: integrated circuits; laser fault attack; Hardware security; benchmark suite